STRATEGY TO MASK THE BITTER TASTE OF MOMORDICA CHARANTIA EXTRACT USING ALGINATE–GELATIN BEADS - Sutriyo; Iswandana, Raditya; Fauzi, Fauzana (International Journal of Applied Pharmaceutics, 2018)
Objective: This study is aimed to develop a strategy to mask the bitter taste of Momordica charantia Linn. extract using alginate–gelatin beads. Methods: Beads of bitter melon fruit extract (M. charantia Linn) were prepared using an ionic gelation method in which cross-linking occurs between sodium alginate and calcium chloride that serves to mask the bitter taste. Beads were prepared using sodium alginate (1.5% w/v) with various concentrations of bitter melon fruit extract (1:2, 1:1, and 1:0.5), gelatin (2% w/v), and CaCl2 3%. The obtained beads were then characterized both physically and functionally, and their morphology, process efficiency, particle distribution, swelling index, and water content were recorded. Results: Formula 1 beads, with a 1:2 ratio of extract: alginate, displayed a near-round shape with a diameter of 600–1 200 μm, a swelling index of 113.21%, and a moisture content of 15.34%. In addition, these beads were able to significantly cover the bitter taste (p<0.05). Conclusion: Formula 1 beads with a 1:2 ratio of extract: alginate can effectively mask the bitter taste of M. charantia Linn.